2019
DOI: 10.1002/stem.2971
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Human-Animal Neurological Chimeras: Humanized Animals or Human Cells in an Animal?

Abstract: Blastocyst complementation is an emerging methodology in which human stem cells are transferred into genetically engineered preimplantation animal embryos eventually giving rise to fully developed human tissues and organs within the animal host for use in regenerative medicine. The ethical issues surrounding this method have caused the National Institutes of Health to issue a moratorium on funding for blastocyst complementation citing the potential for human cells to substantially contribute to the brain of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 143 publications
0
18
0
2
Order By: Relevance
“…Of particular concern among respondents in the current study is the contribution of human cells in the brain of the pigs and the potential neurological humanization of the animals involved in HACE research ( Crane et al, 2019b ; Sawai et al., 2017b ). Assuming humanization is possible, it would require researchers to contend with both the moral status of the resulting chimeric individual and the consequences of blurred species lines, including potential moral confusion ( Baylis and Robert, 2007 ; HĂŒbner, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern among respondents in the current study is the contribution of human cells in the brain of the pigs and the potential neurological humanization of the animals involved in HACE research ( Crane et al, 2019b ; Sawai et al., 2017b ). Assuming humanization is possible, it would require researchers to contend with both the moral status of the resulting chimeric individual and the consequences of blurred species lines, including potential moral confusion ( Baylis and Robert, 2007 ; HĂŒbner, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…But how likely is it that humanization (however defined) will actually occur? Our recent review of 150 peer-reviewed transplantation studies found that, while a relatively high degree of human-animal neurological chimerism has been observed in multiple studies, there was no evidence to suggest that integration of human neurons within the non-human animal results in humanization ( Crane et al, 2019b ). Thus, although humanization could theoretically be an issue and should remain a focal point of ethical and legal concern when developing a new policy, HACE research currently being conducted has observed very limited contribution of human cells to a non-human animal brain in preterm human-animal chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the ongoing ethical debate surrounding blastocyst complementation, many technical barriers currently need to be addressed. Off-target chimerism with human cells present in the brain or reproductive system of the host animal is one major concern 141 . Conversely, mixed chimerism in the target tissue where animal cells are present within the human organ has also raised concerns over the viability of the transplanted organ, as well as immunologic considerations.…”
Section: Barriers and Challenges To Complementationmentioning
confidence: 99%
“…Groups including the UK Academy of Medical Sciences,13 Japanese Expert Panel on Bioethics14 and German Ethics Council15 have recommended that research involving chimeric animals with humanised brains should be subject to greater restrictions than other forms of chimera research. In the USA, the National Institutes of Health has issued a moratorium on funding for blastocyst complementation as it considers ethical issues raised by the prospect of human cells contributing to chimeric animals’ brains 16. Concerns about chimeric animals’ moral status are most commonly and most forcefully raised regarding brain chimera research involving non-human primates17 18 or other large mammals,13 although some argue that we should not create any chimeras with human-like neuronal structures, regardless of species, due to concerns that such animals would develop human-like consciousness 19.…”
mentioning
confidence: 99%